Representações de estudantes de uma comunidade ribeirinha sobre a floresta amazônica - Souza, Adriana Costa de (2020)
This research aims to identify the representations about the Amazon Forest of the people who live in it, that is, students of the elementary school, looking for relations with their social surroundings and schooling. Thus, the participating school, as it is inserted in the Amazon region, is configured as a favorable place to understand how these students' representations about the Amazon forest are constituted. In a qualitative nature, this investigation is based on (a) the notion of representation from the studies of Hall (1997), immersed in the theoretical field of Cultural Studies; (b) investigation of how the interviewed students learn, through the investigations of Carvalho (2013); and (c) in the phenomenological principles, using the method of analysis described by Giorgi (2010), in order to value the experiences lived by the subjects in the real context in which they live, considering their relationship with him. This research was developed in a municipal school in the city of Manaus, located in a ribeirinha area, on the banks of the Negro River, immersed in a Sustainable Development Reserve (RDS), with the participation of 34 students from the 6th to the 9th grade, of elementary education. To obtain the data, the following instruments were used: collection of pedagogical documents, application of questionnaires and interviews. The data analysis process runs through two moments: contextual and analytical. From this research, it can be concluded that the school, as one of the educational instances, constituting knowledge, can contribute to the emancipation of the riverside peoples, offering an education that respects their diversity. In addition, science education, as a field of knowledge, can take on new structures in favor of demystifying stereotypes, generalizations about the Amazon Forest and its population.